The implications of training in self-efficacy beliefs of technical-administrative managers in a federal institution of higher education - Cavalcante, Keliane de Oliveira; Silva, Anielson Barbosa da (Revista de Administração da UFSM, 2017)
The article aims to analyze the implications of training in self-efficacy beliefs of technical-administrative managers of a Federal institution of higher education (IFE). The research is qualitative in nature and was realized with 12 managers, using semi-structured interviews. The discourse analysis revealed perceptions of the subject on the implications of training in the beliefs of self-efficacy and in the development of competences. The survey results reveal the necessity of the IFE include in training processes, beyond the notion of competences, an analysis of managers' beliefs about their capabilities, through the exploration of self-efficacy construct as determinant in the planning of the actions of managerial development. About the links between the level of self-efficacy and managers training, it is concluded that the managers surveyed generate a positive impact in their work because on their self-efficacy beliefs, since the experiences contributed to give more security in carrying out the activities and helped them deal with the difficult situations and problem-solving processes. The study is expected to assist in the introduction of self-efficacy as a key construct in managerial development programmes.